2019
DOI: 10.1101/824896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leveraging multiple layers of data to predict Drosophila complex traits

Abstract: 1 An important challenge in genetics is to be able to predict complex traits accurately. Despite 2 recent advances, prediction accuracy for most complex traits remains low. Here, we used the 3 Drosophila Genetic Reference Panel (DGRP), a collection of 200 lines with whole-genome 4 sequences and deep RNA sequencing data, to evaluate the usefulness of using high-quality gene 5 expression levels compared to relying on genotypes for predicting three complex traits. We 6 found that expression levels provided higher… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 44 publications
6
25
2
Order By: Relevance
“…These results are similar to those of a previous study (Morgante et al, 2019), but higher than the results in (Li et al, 2019). This may be due to the quality control of the SNPs, the number of lines, and the line means for phenotypes in the present study, which are the same as those used in (Morgante et al, 2019) and different from those in (Gao et al, 2017). The high heritability of the analyzed traits showed that most loci that affect the traits have additive gene actions or contributions from non-additive gene actions at many loci.…”
Section: Total Genomic Heritability and Prediction Accuracysupporting
confidence: 93%
See 4 more Smart Citations
“…These results are similar to those of a previous study (Morgante et al, 2019), but higher than the results in (Li et al, 2019). This may be due to the quality control of the SNPs, the number of lines, and the line means for phenotypes in the present study, which are the same as those used in (Morgante et al, 2019) and different from those in (Gao et al, 2017). The high heritability of the analyzed traits showed that most loci that affect the traits have additive gene actions or contributions from non-additive gene actions at many loci.…”
Section: Total Genomic Heritability and Prediction Accuracysupporting
confidence: 93%
“…We found that the heritability of the analyzed traits was very high, especially for starvation resistance, which almost explains the whole phenotypic variability in both the female and male lines (Table 1). These results are similar to those of a previous study (Morgante et al, 2019), but higher than the results in (Li et al, 2019). This may be due to the quality control of the SNPs, the number of lines, and the line means for phenotypes in the present study, which are the same as those used in (Morgante et al, 2019) and different from those in (Gao et al, 2017).…”
Section: Total Genomic Heritability and Prediction Accuracysupporting
confidence: 88%
See 3 more Smart Citations